Relative severity of fumonisin contamination of cereal crops in West Africa - Vismer, H.; Shephard, G.S.; Rheeder, J.P.; Westhuizen, L. van der; Bandyopadhyay, Ranajit (Informa UK Limited, 2015)
Traditional and improved varieties of maize, pearl millet and sorghum were planted by small-scale farmers under the direction of the International Institute for Tropical Agriculture in two Nigerian agro-ecological zones: the Sudan Savanna and the Northern Guinea Savanna. Samples were collected for the determination of Fusarium infection and fumonisin (B1, B2 and B3) contamination. A previous paper reported Aspergillus infection and aflatoxin contamination of these samples. Fusarium infection levels, measured by per cent kernels infected, were modest with mean levels for the above cereals of 16% ± 11% (SD), 12% ± 7% and 13% ± 16%, respectively. However, the Fusarium species recovered from maize were predominantly the fumonisin producers F. verticillioides and F. proliferatum, together making an infection rate of 15% ± 10%, whereas these species were present to a limited extent only in the other two cereals, 1% ± 1% for pearl millet and 2% ± 6% for sorghum. Fumonisin contamination was variable but reflected the diversity of Fusarium producers in these three cereals. Mean levels were 228 ± 579 µg kg–1 (range < 5–2860 µg kg–1) for maize, 18 ± 7 µg kg–1 (range = 6–29 µg kg–1) for pearl millet and 131 ± 270 µg kg–1 (range < 5–1340 µg kg–1) for sorghum. Together with previous results on aflatoxin, this study confirmed the co-occurrence of aflatoxins and fumonisins in maize as well as in the traditional African cereals, millet and sorghum (89% co-occurrence across all three cereals). The low fumonisin levels may be ascribed to the use of good agricultural practices. Of the Fusarium species present, those in maize consisted mainly of fumonisin producers, the opposite of what was observed in pearl millet and sorghum. It is concluded that replacement of maize by pearl millet and sorghum could improve food safety with regards to aflatoxin B and fumonisin B exposure.